A Nationwide Cohort Study of Nonrandom Mating in Schizophrenia and Bipolar Disorder. (27th March 2021) - Greve, Aja Neergaard; Uher, Rudolf; Als, Thomas Damm; Jepsen, Jens Richardt Møllegaard; Mortensen, Erik Lykke; Gantriis, Ditte Lou; Ohland, Jessica; Burton, Birgitte Klee; Ellersgaard, Ditte; Christiani, Camilla Jerlang; Spang, Katrine S; Hemager, Nicoline; et al.
Abstract: Nonrandom mating in parents with schizophrenia or bipolar disorder increases the population-level genetic variance among the offspring generation and creates familial (risk) environments likely to be shaped by specific conditions. The objective of this study was to investigate the occurrence of mental disorder and levels of cognitive and social functioning in individuals who have children by partners with schizophrenia or bipolar disorder compared to controls. The Danish High Risk and Resilience Study VIA 7 is a population-based cohort study conducted in Denmark between 2013 and 2016. This study focus on parents diagnosed with schizophrenia ( n = 150) or bipolar disorder ( n = 100) and control parents ( n = 182), as well as their partners without schizophrenia or bipolar disorder ( n = 440). We used linear mixed-effect models, and main outcomes were mental disorders, intelligence, processing speed, verbal working memory, and social functioning. We found that parents having children by a partner with schizophrenia or bipolar disorder more often fulfilled the criteria for a mental disorder and had poorer social functioning compared to parents having children by a partner without schizophrenia or bipolar disorder. Furthermore, parents having children by a partner with schizophrenia performed poorer on processing speed compared to parents in the control group. The presence of nonrandom mating found in this study has implications for our understanding of familial transmission of these disorders and our findings should be considered in future investigations of potential risk factors for children with a parent with schizophrenia or bipolar disorder.